Effects of Phthalate Mixtures on Ovarian Folliculogenesis and Steroidogenesis - Endia J. Fletcher; Ramsés Santacruz-Márquez; Vasiliki E. Mourikes; Alison M. Neff; Mary J. Laws; Jodi A. Flaws (Toxics, 2022)
The female reproductive system is dependent upon the health of the ovaries. The ovaries are responsible for regulating reproduction and endocrine function. Throughout a female’s reproductive lifespan, the ovaries undergo continual structural changes that are crucial for the maturation of ovarian follicles and the production of sex steroid hormones. Phthalates are known to target the ovaries at critical time points and to disrupt normal reproductive function. The US population is constantly exposed to measurable levels of phthalates. Phthalates can also pass placental barriers and affect the developing offspring. Phthalates are frequently prevalent as mixtures; however, most previous studies have focused on the effects of single phthalates on the ovary and female reproduction. Thus, the effects of exposure to phthalate mixtures on ovarian function and the female reproductive system remain unclear. Following a brief introduction to the ovary and its major roles, this review covers what is currently known about the effects of phthalate mixtures on the ovary, focusing primarily on their effects on folliculogenesis and steroidogenesis. Furthermore, this review focuses on the effects of phthalate mixtures on female reproductive outcomes. Finally, this review emphasizes the need for future research on the effects of environmentally relevant phthalate mixtures on the ovary and female reproduction.